New considerations about meaning of the form and the conventional symbols found on monetary tokens (6th-5th centuries bc) - Talmaţchi, Gabriel Mircea (Acta Archaeologica Lodziensia, 2018)
One of the main questions to be put to the evidence is what is the connection between the shape of monetary signs in use and everyday reality in the sixth and fifth centuries BC. Also, if they were commercial items, what was their significance, because they don’t fully express the function of currency? Were they made in the shape of arrowheads without ultimately symbolizing anything of the purpose for which they were created? In fact, ‘arrowhead’ monetary signs represent measurable symbols, used in real trade transactions as a ‘standard’ in certain regions. They were established to act as a counterpart for quantities of goods, which were at the time in question grain and fish products. These two commodities seem to be the most sought after by the local population of Greek origin population. These monetary signs could represent, after a primary connection had been established by spindle-shaped arrowheads, through other stages too throughout the second half of the 6th century BC, evolve into other shapes, in the classic cases representations in the shape of cereal grain, or marine fish respectively. Our opinion is that the interpretation of these signs must have been unequivocal for the population of 6th and 5th centuries BC, or, more precisely the interpretation of their significance and destination. Here we are not referring to real arrowheads used in battle. In casting these monetary signs items the elements which were selected for local exchange were depicted in a selected shape. This means that the simplest one, an arrowhead, represents this symbolically, it is not a real weapon. They represent instead the exchange items for which they were created: cereals-wheat ears or wheat and barley grains, fishery products etc. These new considerations were suggested to us by the study of the monetary symbolism throughout the Greek world. Special attention has been given to the presence, on some of the “arrowhead” monetary signs of the first type (especially the cast monetary signs), of a series of symbols that could be linked, it is assumed, to some monetary workshops of the West-Pontic colonies. They appear chiefly, if not in their entirety, on the “arrowhead” signs in the shape of a laurel leaf, with elongated form with a prominence of central rib and edge.